POLITENESS IN THE VIRTUAL PUBLIC SPHERE: A PRAGMATIC STUDY OF YOUTUBE COMMENTS ON PRAGERU’S VIDEO: ‘ISRAELIS OR PALESTINIANS – WHO’S MORE TOLERANT?’ - Yanti, Yusrita; Wulandari, Sisky (TELL - US JOURNAL, 2025)
This research seeks to analyze politeness strategies used by YouTube commenters in response to PragerU’s “Israelis or Palestinians – Who’s More Tolerant?”, a discussion about the contentious Israel-Palestine issue. Brown and Levinson’s (1987) Politeness Theory is the principal theoretical basis, as supported by Herring’s (2004) Computer-Mediated Discourse Analysis (CMDA) in order to investigate the way in which digital users manage face, identity, and ideology in online political discourse. A qualitative descriptive approach was used with 100 comments purposively selected between September 2022 and September 2024. Comments were attributed to one of four politeness strategies: positive politeness, negative politeness, bald-on-record, and off-record, and interpreted for ideological organizational positioning. The results suggest that positive politeness, which is dominated by pro-Israel users, contributes to creating solidarity and reinforcing group cohesiveness, while negative politeness, which is more noticeable in the pro-Palestinian and neutral comments, downplays conflict and creates social distance. Bald on-record, strategies enable direct ideological claims; off-record strategies (irony, sarcasm) contribute to indirect criticism of other beliefs. The results indicate that politeness strategies in YouTube comments are used as cultural and social resources to manage relationships and express ideas as influenced by anonymity, asynchrony, and the affective dimensions of the medium. This paper draws out the implications of politeness theory online and demonstrates how politeness theory can inform identity construction and discourse polarization in politically sensitive digital environments.